Predictors of Functional Communication Outcomes in Children With Idiopathic Motor Speech Disorders. - Namasivayam, Aravind K.; Hyunji Shin; Nisenbaum, Rosane; Pukonen, Margit; van Lieshout, Pascal (Journal of Speech, Language & Hearing Research)
Purpose: The purpose of the study was to investigate child- and interventionlevel factors that predict improvements in functional communication outcomes in children with motor-based speech sound disorders. Method: Eighty-five preschool-age children with childhood apraxia of speech (n = 37) and speech motor delay (n = 48) participated. Multivariable logistic regression models estimated odds ratios and 95% confidence intervals for the association between minimal clinically important difference in the Focus on the Outcomes of Communication Under Six scores and multiple child-level (e.g., age, sex, speech intelligibility, Kaufman Speech Praxis Test diagnostic rating scale) and intervention-level predictors (dose frequency and home practice duration). Results: Overall, 65% of participants demonstrated minimal clinically important difference changes in the functional communication outcomes. Kaufman Speech Praxis Test rating scale was significantly associated with higher odds of noticeable change in functional communication outcomes in children. There is some evidence that delivering the intervention for 2 times per week for 10 weeks provides benefit. Conclusion: A rating scale based on task complexity has the potential for serving as a screening tool to triage children for intervention from waitlist and/or determining service delivery for this population.